MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN TEKNIK KLOS - Risnayati, Cik (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The purpose of this paper is to describe techniques to improve students' abilities in reading learning, especially reading comprehension through the clos technique. As for the background of this writing because the ability to understand the content of reading in grade 6 SD Negeri 1 Tanjung Raya is very low, while reading has a very important role in the world of education. The ability to understand reading will determine the quality and success of a student as a student in his studies, because all subjects are closely related to reading. By having the ability to understand quality readings, a person can master science, so that poor reading habits have a negative impact on a student. To overcome this, the teacher's effort and creativity are needed. The application of the Clozure technique in learning to read is an effort to train students' comprehension and ability in reading comprehension. The application of the klos technique is carried out by giving students the task of reading silently a discourse in full concentration, with the specified time, after the specified time the reading is taken by the teacher, then students are given another text with the same text but certain parts have been removed to be completed by students so that it becomes read as before.